2018
DOI: 10.1523/jneurosci.3481-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Neuron Populations Represent Sequences of Behavioral Epochs During Both Execution and Observation

Abstract: Mirror neurons (MNs) have the distinguishing characteristic of modulating during both execution and observation of an action. Although most studies of MNs have focused on various features of the observed movement, MNs also may monitor the behavioral circumstances in which the movement is embedded, including time periods preceding and following the observed movement. Here, we recorded multiple MNs simultaneously from implanted electrode arrays as two male monkeys executed and observed a reach, grasp, and manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 52 publications
8
54
4
Order By: Relevance
“…However, an alternative method which seeks to circumvent this by constraining random subspaces to the covariance structure of the full dataset (Elsayed et al, 2016) is biased towards identifying orthogonality between two different subspaces, due to regression to the mean within the null distribution. The finding that execution and observation are more overlapping in F5 is consistent with recent work demonstrating MirN activity in ventral premotor cortex (PMv) and M1 during execution of reach and grasp to be associated with a series of hidden states, which were recapitulated during observation in PMv, but not M1 (Mazurek et al, 2018). Overall, although M1 neurons can be active during both execution and observation, the pattern of this activity at the population level was quite different between the two conditions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, an alternative method which seeks to circumvent this by constraining random subspaces to the covariance structure of the full dataset (Elsayed et al, 2016) is biased towards identifying orthogonality between two different subspaces, due to regression to the mean within the null distribution. The finding that execution and observation are more overlapping in F5 is consistent with recent work demonstrating MirN activity in ventral premotor cortex (PMv) and M1 during execution of reach and grasp to be associated with a series of hidden states, which were recapitulated during observation in PMv, but not M1 (Mazurek et al, 2018). Overall, although M1 neurons can be active during both execution and observation, the pattern of this activity at the population level was quite different between the two conditions.…”
Section: Discussionsupporting
confidence: 90%
“…While the roles of F5 and M1 during the execution of visually-guided grasp have been studied extensively (Umiltá et al, 2007; Davare et al, 2008; Schaffelhofer & Scherberger, 2016), a more systematic understanding of the differences between action execution and observation activity in these two key nodes in the grasping circuitry could provide important insights into dissociations between representation of potential actions at the cortical level, and recruitment of descending pathways and muscles for actual action execution (Schieber, 2011). Along these lines, recent work comparing MirNs in premotor and motor cortex found premotor MirNs, but not those in M1, showed similar state transitions in execution and observation (Mazurek et al, 2018). State-space analyses have also previously found that F5 and the upstream anterior intraparietal area (AIP) exhibit different dynamics during immediate and delayed grasping actions (Michaels et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…While the roles of F5 and M1 during the execution of visually-guided grasp have been studied extensively ( Umilta et al, 2007 ; Davare et al, 2008 ; Schaffelhofer and Scherberger, 2016 ), a more systematic understanding of the differences between action execution and observation activity in these two key nodes in the grasping circuitry could provide important insights into dissociations between representation of potential actions at the cortical level, and recruitment of descending pathways and muscles for actual action execution ( Schieber, 2011 ). Along these lines, recent work comparing MNs in premotor and motor cortex found premotor MNs, but not those in M1, showed similar state transitions in execution and observation ( Mazurek et al, 2018 ). State-space analyses have also previously found that F5 and the upstream anterior intraparietal area (AIP) exhibit different dynamics during immediate and delayed grasping actions ( Michaels et al, 2018 ).…”
Section: Introductionmentioning
confidence: 91%
“…At the spinal level, PTNs not only excite motoneurons via cortico-motoneuronal (CM) projections ( Porter and Lemon, 1993 ; Rathelot and Strick, 2006 ), but also exert indirect effects via segmental interneuron pathways, which in turn display their own complex activity before and during movement ( Prut and Fetz, 1999 ; Takei and Seki, 2013 ). A dynamical systems approach ( Shenoy et al, 2013 ) has recently suggested that movement-related activity unfolds in largely orthogonal dimensions to activity during action preparation, such that movement is implicitly gated during movement preparation ( Kaufman et al, 2014 ; Elsayed et al, 2016 ), and a similar mechanism has been hypothesised to operate during action observation ( Mazurek et al, 2018 ) and action suppression ( Pani et al, 2019 ). While the roles of F5 and M1 during the execution of visually-guided grasp have been studied extensively ( Umilta et al, 2007 ; Davare et al, 2008 ; Schaffelhofer and Scherberger, 2016 ), a more systematic understanding of the differences between action execution and observation activity in these two key nodes in the grasping circuitry could provide important insights into dissociations between representation of potential actions at the cortical level, and recruitment of descending pathways and muscles for actual action execution ( Schieber, 2011 ).…”
Section: Introductionmentioning
confidence: 99%